1976
DOI: 10.1111/j.1540-5915.1976.tb00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Sum Losses in Operational Forecasting

Abstract: In operational applications, forecasts .are normally adjusted by applying safety factors to allow for asymmetry in the underlying loss function. This paper considers an extension of the often used linear loss function to situations in which an error can also result in a fixed sum loss.The need for forecasts as inputs to planning and decision models is widely recognized. Forecasts range from subjective, qualitative predictions of the long range future to short range operational projections which are quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Furthermore, they indicated that mixing of objective and subjective forecast information would produce the best overall earnings forecast over a period of time. Willis (1976) in a theoretical study analyzed the economic losses associated with forecast errors and found that they are not symmetric. He noted that forecast revisions allowing for asymmetry should be integrated into the forecasting methodology.…”
mentioning
confidence: 98%
“…Furthermore, they indicated that mixing of objective and subjective forecast information would produce the best overall earnings forecast over a period of time. Willis (1976) in a theoretical study analyzed the economic losses associated with forecast errors and found that they are not symmetric. He noted that forecast revisions allowing for asymmetry should be integrated into the forecasting methodology.…”
mentioning
confidence: 98%
“…They suggested that a method to overcome random variation in the earnings series was required to improve forecast accuracy. Willis [35] analyzed the economic losses associaled with forecast errors and found they are not symmetric. He suggested that forecast revisions allowing for asymmetry should be integrated into forecasting methodology.…”
Section: Introductionmentioning
confidence: 99%